Adipose Tissue Mediates Associations of Birth Weight with Glucose Metabolism Disorders in Children. Issue 5 (27th February 2019) - Wu, Yunpeng; Yu, Xinting; Li, Yu; Li, Ge; Cheng, Hong; Xiao, Xinghua; Mi, Jie; Gao, Shan; Willi, Steven M.; Li, Ming
Abstract : Objective: This study aimed to examine the associations between low birth weight (LBW) versus high birth weight (HBW) and dysglycemia, including insulin resistance (IR) and impaired fasting glucose (IFG) in children, and aimed to explore the role of adipose tissue in these relationships. Methods: A total of 2, 935 subjects aged 6 to 18 years were recruited to examine the relationship between birth weight and IR (defined as homeostasis model assessment of IR  >  2.3) and IFG. Mediation analyses were conducted to examine the roles of various adipokines and anthropometrics in these relationships. Results: Children with LBW had a nearly twofold increased risk of IR and IFG compared with children with normal birth weight, even after adjusting for BMI. Decreased circulating adiponectin levels contributed to 21.2% of the LBW–IR relationship, whereas none of the selected adipose markers mediated the LBW–IFG relationship. In contrast, after controlling for current BMI or waist circumference, HBW reduced the risk of IR by 34%, but it was not associated with IFG. The HBW–IR relationship was significantly mediated by reduced leptin levels (21.4%) and fat mass percentage (8.8%), after controlling for BMI. Conclusions: These findings suggest the potential role of adipose tissue dysfunction as an underlying mechanism for the birth weight–type 2 diabetes relationship.